Formulasi Kebijakan Kriminal Dalam Menjerat Pelaku Pengguna Jasa Prostitusi Online - Ari Sudewo, Fajar (Universitas Pancasakti Tegal, 2022)
The phenomenon of online prostitution has become news viaral lately as the arrest of both artists, and ordinary people, but the law has not regulated how to ensnare users of online prostitution, for that it takes a criminal policy oriented in ensnaring all individuals involved in online prostitution. The problem in writing this Journal is (a) Ideal law enforcement as a criminal policy step in ensnaring online prostitution service users in Bandar Lampung City, (b) efforts to sanction criminals to perpetrators of online prostitution service users in criminal law policy? The research uses an empirical juridically and juridically normative approach. The results of the study showed that. Ideal law enforcement in the efforts of criminal policy in ensnaring the perpetrators of online prostitution service users in Bandar Lampung City Although there are no special provisions governing the users of PSK services in the Criminal Code, law enforcement applies the article of adultery if the psk customer already has an official partner (on the basis of marriage), and then the spouse complains about the actions of his partner who uses psk services, then the person using the services of the PSK can be ensnared with the article of Adultery stipulated in Article 284 of the Criminal Code and also Article 60 of the Regulation Bandar Lampung City Area Number: 01 of 2018 concerning Public Peace and Public Order which is a criminal threat of imprisonment of a maximum of 3 (three) months or a maximum fine of Rp 50,000,000.00 (fifty million rupiah) and efforts to sanction criminal sanctions to perpetrators of online prostitution services here researchers see that the Indonesian Government's own policy does not expressly prohibit the practice of prostitution, Because the arrangement regarding the criminal act of online prostitution does not regulate the provisions regarding criminal sanctions for users of commercial sex services, so users of online prostitution services cannot be criminally accounted for, and those who use the services of commercial sex workers can freely without fear of criminal legal sanctions. Law enforcement is weak